Ngerambat Gending: A Composition of Essential Idea of Karawitans Definition | Ngerambat Gending: Sebuah Komposisi dari Ide Esensi Definisi Karawitan - Pande Kadek Ega Sasdicka; I Nyoman Kariasa (GHURNITA: Jurnal Seni Karawitan, 2021)
There is still a gap of vocal use separators in various Balinese karawitan compositions that develop lately, such as; Sandya gita, Gegitaan and Gegerongan. Karawitan composition "Ngerambat Gending '' presents a new perspective, that is combining the connection between instrumental and consistently. Indirectly without the instrument this artwork cannot be crystallized as well as the opposite without the vocal this work also cannot be realized. The same proportion of work on both instruments and vocals into a whole unit composition, is a "leading" thing in the creation of Bali's karawitan. The goal to be achieved in this work is to actualize an idea based on the essence of the definition of karawitan itself. To materialize this work, the composer combined the process of compiling the work by Pande Made Sukerta with the creation methods of I Wayan Bratha and I Wayan Dibia. Processed from the work of Ngerambat Gending, the composer tries to make connections between instruments with other instruments, instruments with vocals and vocals with vocals which are divided into structures. The “Ngerambat Gending'' karawitan composition  was successfully transformed by using a structure using the names of the musical patterns that the composer made part of the structure into the work itself, such as, gegineman, pengadeng, gegacangan, gegenderan and penyuud.